2007
DOI: 10.1159/000108755
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Major Outcomes, Risk Factors, Prevention and Management of Chronic Kidney Disease in China

Abstract: Chronic kidney disease (CKD) is common in China. In residents older than 40 years in Beijing, China, 11.3% of subjects had at least one indicator of kidney damage. The primary cause of chronic renal failure in China was glomerulonephritis, which was followed by diabetic nephropathy and hypertensive nephrosclerosis. Renal failure, cardiovascular disease and infection were important complications. IgA nephropathy (IgAN) is the most common CKD in China. The prevalence of hypertension, intrarenal artery lesions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
54
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 55 publications
8
54
0
1
Order By: Relevance
“…3;2018 increase of proteinuria and the risk for proteinuria according to systolic and diastolic blood pressure were significantly increased beginning at levels of 110 and 90 mmHg, respectively (Ramirez et al, 2002). Hypertensive nephrosclerosis was the third most common causes of KD (Xie & Chen, 2008). High blood pressure (L. Xue et al, 2014) and hypertension (W. Chen et al, 2009;W.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…3;2018 increase of proteinuria and the risk for proteinuria according to systolic and diastolic blood pressure were significantly increased beginning at levels of 110 and 90 mmHg, respectively (Ramirez et al, 2002). Hypertensive nephrosclerosis was the third most common causes of KD (Xie & Chen, 2008). High blood pressure (L. Xue et al, 2014) and hypertension (W. Chen et al, 2009;W.…”
Section: Discussionmentioning
confidence: 98%
“…A study in Singapore revealed that diabetes associated with increase of proteinuria (Ramirez et al, 2002). The most common cause of KD was glomerulonephritis and the second was diabetic nephropathy (Xie & Chen, 2008). The study revealed that blood sugar (HbA1c) in diabetes patients was associated with an increase of albuminuria, predictor of microvascular lesions for kidney disease including ESRD (Parving et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…[10,11] IgAN is the most common form of primary glomerulonephritis among patients undergoing renal biopsy and is also one of the major causes of secondary malignant hypertension and ESRD. [20][21][22][23][24] In patients with IgAN-MHT, we previously found that the ischemic lesions and the glomerular background lesions both contributed to the impairment of renal function at presentation. [11] In the literature, it was reported that the genetic variants in the chromogranin A promoter were not only associated with hypertension, but also with hypertensive ESRD in primary hypertension [7,8] ; therefore, whether CHGA gene genetic variants affect onset of malignant hypertension and target-organ damage in secondary MTH raised special interest.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study made between 2007 and 2009 found that regional variation exists in the prevalence of dialysisrequiring acute kidney injury in the United States [11]. In China for example, an epidemiologic study of chronic kidney disease suggest significant differences between urban districts (e.g., hematuria in 0.8% of the population in the district of Beijing and in 6.5% in the city of Guangzhou [12]). Chronic tubulointerstitial disease has also similar geographic prevalence.…”
Section: Figure 3 -Getis-ord Gi* Statistic Was Used On the Ratio Betwmentioning
confidence: 99%